2004
DOI: 10.1007/s00264-004-0573-y
|View full text |Cite
|
Sign up to set email alerts
|

Patient-perceived outcome measures following unicompartmental knee arthroplasty with mini-incision

Abstract: We reviewed 150 patients (183 knees) who underwent mini-incision unicompartmental knee arthroplasty (Oxford). Mean age was 71.5 (36-92) years. Review was conducted at least 12 months following surgery. To assess results, we used the Oxford knee questionnaire, modified Grimby score, return to sport and work, knee "normality" and patient general health. The mean Oxford knee score was 22.17 (range 12-54). Kneeling scored worse than other activities. No significant age or gender difference was found. Mean modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 19 publications
2
21
2
Order By: Relevance
“…Nevertheless, the fact that most patients followed our recommendation to stop high impact sports after UKA surgery is a limitation of our study, as the recommendation limits the choices of sports activities that are advisable after UKA. The KSS, WOMAC, OKS and the patient's satisfaction after the UKA surgery yielded better results in the active patient group, which is consistent with the study by Jahromi et al [10] and Fisher et al [6]. The active patients tended to have less pain.…”
Section: Discussionsupporting
confidence: 82%
“…Nevertheless, the fact that most patients followed our recommendation to stop high impact sports after UKA surgery is a limitation of our study, as the recommendation limits the choices of sports activities that are advisable after UKA. The KSS, WOMAC, OKS and the patient's satisfaction after the UKA surgery yielded better results in the active patient group, which is consistent with the study by Jahromi et al [10] and Fisher et al [6]. The active patients tended to have less pain.…”
Section: Discussionsupporting
confidence: 82%
“…Other independent centres reported slightly inferior scores (AKS 71−91 points) [9,13,23]. However, our results are not quite on a par with the excellent results in the designer series studied in Oxford [20,24].…”
Section: Discussioncontrasting
confidence: 55%
“…Therefore, we are confident the changes to the technique and small refinements to the implant design have decreased the early failure and increased the excellent outcomes we have seen. While several authors reported no difference in the Knee Society overall scores or KS functional scores at 4, 5, or 10 years postoperatively, little has been published on the early functional outcomes of UKA as compared to TKA [1,3,16,25,34,41]. This study demonstrated the difference with improved early functional outcomes on multiple levels.…”
Section: Discussionmentioning
confidence: 51%
“…While patients can expect a durable implant with good long-term survivorship, achievement of short-term goals has come under increased focus [4,6,16,21,29,31,42]. To enhance patient outcomes with knee arthroplasty, we suggest a multimodal approach to optimize functional recovery must be implemented.…”
Section: Introductionmentioning
confidence: 99%